Comfort and functionality of pregnant women’s feet: study of kinetic parameters with silicon insoles - Marques, Alda (2005)
Pregnant women can suffer pains and muscle-skeletal injuries in their feet, lower limbs and vertebral column, due to physiological and biomechanic changes during pregnancy. In this study we assessed the pain and comfort of the feet during gait: without silicone insoles (for pregnant and non-pregnant women); using hindfoot insoles and complete insoles (only for pregnant women). We also measured the plantar pressure distribution, the ground reaction forces and the duration of the gait cycle (for pregnant women with and without insoles; and for non-pregnant women without insoles). Results showed that pregnant women take a significantly (1± 0,05 e 0,95±0,08 seconds right and left foot respectively vs 0,87±0,07 e 0,86±0,08 seconds of the control group, p=0,001 right foot and p=0,03 left foot) longer time to complete the stance phase, and have significantly (Visual Analogue Scale - 4,79) more pain and discomfort in the feet, than non-pregnant women (2,93), p=0,03. Pregnant women preferred the complete silicone insole because these redistributed ground reaction forces (eg: vertical component without insole vs complete insole, 1,07±0,02 to 1,07±0,03 right foot, p=0,831, 1,08±0,03 to 1,06±0,03 left foot, p=0,319) and pressure (eg. without insole vs complete insole: 0,68±0,50 to 0,81±0,28 right foot, p=0,028 and 0,43±0,13 to 0,68±0,27 left foot, p=0,003 or 4,83±1,24 to 4,59±1,33 right foot, p=0,774 and 5,16±0,81 to 4,30±0,62 left foot, p=0,118) and increased the contact area of the feet with the ground (eg. without insole vs complete insole: 13,13± 5,57 to 18,82±3,58 right foot, p=0,001, 10,68±3,91 to 15,85±5,50 left foot, p=0,001). Results suggest that we can relief the pain and discomfort that pregnant women feel in their feet during gait, using a complete silicone insole.